2017
DOI: 10.1177/2192568217710854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Health-Related Quality of Life and Disability at 1 Year After Surgery for Thoracolumbar Burst Fractures

Abstract: Study Design:Case series.Objective:Thoracolumbar burst fractures (TLBF) are the most frequent type of spinal fractures. Approximately half of the patients are neurologically intact and their treatment is still debatable. Gender could influence outcome after surgical procedures, but this is still unclear in patients sustaining a spinal fracture. The aim of this study was to investigate how gender influences health-related quality of life (HRQOL) and disability in patients operated on for TLBF.Methods:We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Of the 35 studies where sex/gender differences were present, n = 3 were on spine fractures after spinal fusion surgery. One study was on sacral fractures ( 54 ), and two studies were on thoracolumbar burst fractures ( 34 , 42 ). Salzmann et al observed, at a 6-month follow-up, that female gender (76.2%), advanced age (mean, 66.4 years), and obesity were risk factors for post-op sacral fractures ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 35 studies where sex/gender differences were present, n = 3 were on spine fractures after spinal fusion surgery. One study was on sacral fractures ( 54 ), and two studies were on thoracolumbar burst fractures ( 34 , 42 ). Salzmann et al observed, at a 6-month follow-up, that female gender (76.2%), advanced age (mean, 66.4 years), and obesity were risk factors for post-op sacral fractures ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Differently, Jang et al showed that the male gender was a risk factor for recollapse of thoracolumbar burst fractures ( 34 ). At 1-year follow-up, Maior et al reported that male patients have better outcomes than females after thoracolumbar burst fractures; an increased score in each item of the SF-36 in male than female patients was also observed ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could cause a different interpretation of a similar disability and degree of pain between the 2 genders. In a previous study investigating the issue of this correlation after surgery for thoracolumbar burst fractures, we found a higher association between disability and HRQoL in female patients [ 23 ]. In this study, ODI and PCS correlated significantly at 1 year after surgery.…”
Section: Discussionmentioning
confidence: 94%